NOKEN LITERATION: A WISDOM LOCAL IN IMPROVING INVESTMENT AWARENESS COMMUNITIES - Wike Juniati (Universitas Airlangga, 2019)
Noken literacy is a local wisdom program implemented by a literacycommunity in the land of Papua. This program was initiated with theaim of increasing the understanding of people in Papua about financialliteracy. The method of implementation is by conducting field trips anddirect assistance to the people involved in the economic activities of themarket center in the Jayapura area. What distinguishes this programfrom other programs is because of the uniqueness of the objects carriedby literacy activists when they go down to the field, namely a noken bag.Noken is one type of typical Papuan bag that has many philosophiesabout the Papuan people. It is hoped that the approach to using thisunique bag of Papua will make people interested in understanding aboutfinancial literacy carried out by literacy activists. So that the decline ofliteracy and financial inclusion in the Sharia capital market in Papuacan be overcome.